2009
DOI: 10.1136/thx.2009.121459
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal acetaminophen exposure and risk of wheeze at age 5 years in an urban low-income cohort

Abstract: Background-Acetaminophen has been associated with asthma and is in part metabolised via the glutathione pathway. Inner-city minority children have high asthma morbidity and a relatively high frequency of a minor allele variant in the glutathione S transferase Pi gene (GSTP1). We hypothesised that prenatal acetaminophen exposure would predict wheeze at age 5 years in an inner-city minority cohort and examined whether this association was modified by common polymorphisms in genes related to the glutathione pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
5
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 35 publications
3
85
5
1
Order By: Relevance
“…Paracetamol depletes glutathione levels, potentially facilitating airway damage and disease. Studies have suggested that paracetamol exposure at various stages of life increases asthma risk [11,21,38]. Assessment of paracetamol consumption has varied between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracetamol depletes glutathione levels, potentially facilitating airway damage and disease. Studies have suggested that paracetamol exposure at various stages of life increases asthma risk [11,21,38]. Assessment of paracetamol consumption has varied between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have supported early life origins for childhood and early adult asthma [9][10][11][12][13][14][15][16]. More recently, attention has turned to early life as also being of possible relevance for the development of COPD [9,17,18].…”
mentioning
confidence: 99%
“…29 A cohort study that evaluated the use of paracetamol during pregnancy observed that the use of this drug was associated with the presence of asthma at age five and the risk was higher in those who had a greater number of days of consumption, suggesting a possible dose-dependent association. 30 Therefore, the association between paracetamol and wheezing/asthma may simply reflect a reverse causality, i.e. children with a genetic predisposition to asthma or other allergies are more prone to febrile comorbidities, particularly URTI and therefore use more antipyretic medications such as acetaminophen.…”
Section: Variablesmentioning
confidence: 99%
“…The link between paracetamol and asthma has been extensively investigated [1,2,3,4,5,6], but the mechanism of hypersensitivity reactions is not well understood [7,8,9,10]. Discovered in 1878 and first used as an antipyretic in 1887, paracetamol has become increasingly popular due to the paucity of its adverse effects in therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%